Forecasting of performance parameters of the sugar house in the sugar factory - Mironchuk, Valeriy; Gulyy, Ivan; Shtangeeva, Nadiya; Yeshchenko, Oksana (My University, 1999)
The universal model of the multistage sugar crystallization has been developed which permits to simulate the multistage crystallization process with the help of the computer with the sufficient degree of detail and sequence sharply corresponding to the real industrial process. The proposed universal model of the sugar crystallization process allows to forecast the parameters of the performance of the sugar house in the sugar factory. The investigations carried out have demonstrated the advantage of the sugar crystallization schemes with the recirculation.
Keywords: crystallization scheme; recirculation; universal model; calculation experiment; crystallization sugar; схема кристалізації; універсальна модель; рециркуляція; обчислювальний експеримент; кристалізація цукрози; схема кристаллизации; рециркуляция; универсальная модель; вычислительный эксперимент; многоступенчатая кристаллизация сахара; кафедра технологічного обладнання та комп’ютерних технологій проектування; кафедра технології цукру і підготовки води